2012
DOI: 10.1152/ajpcell.00336.2011
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous ouabain regulates cell viability

Abstract: The endogenous cardiac steroid-like compounds, endogenous ouabain (EO) in particular, are present in the human circulation and are considered putative ligands of the inhibitory binding site of the plasma membrane Na(+)-K(+)-ATPase. A vast amount of data shows that, when added to cell cultures, these steroids promote the growth of cardiac, vascular, and epithelial cells. However, the involvement of the endogenous compounds in the regulation of cell viability and proliferation has never been addressed experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 57 publications
3
67
0
4
Order By: Relevance
“…13 This effect was now tested on primary human fibroblasts, bovine aortic endothelial cells, and rat smooth muscle cells. The endogenous ouabain present at 0.5 nM in the media was reduced by 87% by treating the culture media with specific anti-ouabain antibodies.…”
Section: Reduction Of Endogenous Ouabain In the Culture Medium Inhibimentioning
confidence: 99%
See 1 more Smart Citation
“…13 This effect was now tested on primary human fibroblasts, bovine aortic endothelial cells, and rat smooth muscle cells. The endogenous ouabain present at 0.5 nM in the media was reduced by 87% by treating the culture media with specific anti-ouabain antibodies.…”
Section: Reduction Of Endogenous Ouabain In the Culture Medium Inhibimentioning
confidence: 99%
“…11,12 We previously found that lowering the endogenous ouabain present in serum-supplemented tissue culture media, by treating the media with specific anti-ouabain antibodies, reduced the viability and growth of several cultured cell lines. 13 This suggested that ouabain serves as a growth factor, a notion that was recently addressed in relation to kidney growth and development. Studies by Li et al showed that the addition of exogenous ouabain to pregnant rats rescues the development of embryonic kidneys in animals given a low-protein diet, suggesting the steroid's role in kidney development.…”
mentioning
confidence: 99%
“…Essas enzimas têm suas atividades reguladas por fatores que podem promover o remodelamento vascular devido a uma maior degradação da matriz extracelular e permitinr a migração e proliferação de células musculares lisas e de células inflamatórias para a parede DMITRIEVA; DORIS, 2003;DVELA et al, 2012; KHUNDMIRI et a.l, 2007; KOMETIANI et al, 1998; KOTOVA et al, 2006; KULIKOV et al, 2007;LIU et al, 2000;MONTERO et al, 1993;MURATA et al, 1996;TREVISI et al, 2006;CAI, 2003;XU et al, 2009). Essa substância endógena vem sendo muito estudada quanto aos mecanismos que descrevem sua abilidade de alterar a reatividade vascular em ratos…”
Section: Figura 1 -Classificação De Artérias Quanto Ao Tipo De Remodeunclassified
“…Além disso, esse gradiente eletroquímico transmembrana também é importante em processos como a contração muscular e a propagação do potencial de ação (LINGEL, 1992 DMITRIEVA;DORIS, 2003;DVELA et al, 2012;KHUNDMIRI et al, 2007;KOTOVA et al, 2006;KULIKOV et al, 2007;MONTERO et al, 1993;MURATA et al, 1996;TREVISI et al, 2006;XU et al, 2009). …”
Section: A Na + K + Atpase E a Ouabaínaunclassified
See 1 more Smart Citation